Pengaruh Konsumsi Energi Sektor Industri, Rumah Tangga, dan Transportasi terhadap Emisi Karbon di Indonesia - Regina Citra Kurnia Pangestu; Anak Agung Ketut Ayuningsasi (Universitas 45 Surabaya, 2024)
Greenhouse gases (GHGs), particularly carbon emissions, are one of the effects of globalization. Consumption of energy for daily activities and necessities influences the rise in carbon emissions. From 1990 to 2021, this study will look at how energy use in the transportation, household, and industrial sectors affects Indonesia's carbon emissions. The research approach is a quantitative one based on secondary time series data sourced from the International Energy Agency (IEA) website. Multiple linear regression analysis methods are used to conduct the analysis. Energy consumption in the household sector has a negative and significant impact on Indonesia's carbon emissions from 1990 to 2021, while energy consumption in the industrial and transportation sectors has a positive and significant impact. The household sector has reduced its use of biomass, switched to electricity and LPG, and implemented energy efficiency. The research suggests that the use of energy in the transportation and industrial sectors has a positive impact due to their continued reliance on fossil fuel-derived non-renewable energy. The fact that an increase in household energy use will result in a decrease in carbon emissions, which can contribute to an improvement in the quality of the environment, indicates that the negative impact of household energy use is actually positive.